Youth apprenticeships in Canada : on their inferior status despite skilled labour shortages - Lehmann, Wolfgang [Verfasser]; Taylor, Alison [Verfasser]; Wright, Laura [Verfasser] (My University, 2014)
"In Canada, youth apprenticeships have been promoted as an educational alternative that leads to the development of valuable skills, allows for the opportunity to earn an income while learning and helps youth to gain a head start into lucrative, creative and in-demand careers. Yet, these programmes have remained rather marginal and continue to be perceived as being of lower-status compared to traditional post-secondary educational pathways, such as those leading to university or community college. In this paper, we draw on interview data with former youth apprentices in the province of Ontario to explore their reasons for entering apprenticeships in high school, their experiences in them and their own perceptions about the status and social recognition of apprenticeships. We suggest that policies regarding apprenticeship programmes in Canada need to expand their focus. While emphasis is currently placed on recruiting students by highlighting relatively utilitarian benefits, we argue that more focus needs to be placed on the training offered to apprentices including the commitment of employers to provide quality training on the job, the integration of classroom and on-the-job training and the opportunity for apprentices to move from partial to full participation in communities of practice." (Autorenreferat; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.3.2 Nordamerika; Berufsausbildung; Beruflicher Status; Arbeitskräftemangel; Handwerk; Kanada